Evaluation of the shielding parameters implemented in the PET-CT facility at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka - Hossain, MN; Mia, MS; Biman, TA; Mehdi, H; Begum, F (Bangladesh Journal of Physics, 2020)
Positron Emission Tomography (PET) combined with Computed Tomography (CT) is a very sensitive diagnostic imaging modality that consists of both functional and anatomical imaging into one combined scanning system. Because of the high energy of annihilation radiation (511 keV) for PET tracers, shielding requirements are an important consideration in the design of a PET/CT facility. The shielding evaluation for adequate radiation protection of a PET/CT facility consists of the assessment of annual effective dose both to occupational workers and to members of the public’s. The overall shielding assessment takes into account the radionuclides activity involved, the facility design, the scanning procedures, the expected number of patients per year and so on. The evaluation also depends upon the size of the PET/CT imaging room and patient’s uptake rooms, the thickness and the physical materials of walls, floors and ceilings. In this work we verified the adequacy of shielding installed in the PET/CT facility at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka. The assessment results were compared to the provided shielding which was the design requirements. Bangladesh Journal of Physics, 26(2), 51-59, December 2019